“We Learned As We Went Like Everyone Else”: Experiences of Librarians Teaching Information Literacy At Canadian Universities During the COVID-19 Pandemic - Goosney, Janet L. (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2024)
The global COVID-19 pandemic led to an unprecedented shift in teaching and learning at Canadian universities as campuses closed, in-person classes were suspended, and institutions transitioned to entirely online modes of instruction. This transition included information literacy librarians, who worked to support the learning and research needs of students during this extraordinary time. In this study, an 18-question survey was distributed to professional librarians at English and bilingual universities throughout Canada to investigate their experiences designing and teaching information literacy instruction from March 2020 to August 2021, when most institutions were closed to in-person instruction. The goal of this study was to gain insight into the needs of survey participants and the challenges they experienced as they transitioned to emergency remote teaching (ERT), the strategies and supports they used to navigate the transition, and the impact of their experiences on their professional and personal lives during the pandemic and into the future. The survey findings reveal that, while most librarians in Canada did not have extensive online teaching experience prior to the pandemic, they made significant changes to their instructional practices to provide continued information literacy support. While most found this transition to be at least moderately challenging, the majority also report that they have benefited from these experiences, expanding their instructional repertoire, gaining confidence in their ability to teach online, and acquiring new skills.